2017
DOI: 10.2134/agronj2016.12.0719
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobically Digested Cattle Manure Supplied More Nitrogen with Less Phosphorus Accumulation than Undigested Manure

Abstract: Solid beef cattle manure is a good anaerobic digestion feedstock for methane production, but more research is needed to determine how co-products of the anaerobically digested manure may be used in crop production, while limiting the risk of nutrient loss to the environment. Over four growing seasons, we measured the N and P supplied to barley (Hordeum vulgare L.) forage test crops from (i) anaerobically digested solid beef cattle manure (digestate), (ii) separated solids from the digestate (separated solids),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
3
17
1
Order By: Relevance
“…Anaerobic digestion of agricultural residues may be considered ecologically sound (Insam et al 2015), but the variation in digestate N concentrations and decomposition of digestate's organic N leads to uncertainties in recommendation rates for agricultural use. Previous studies on digestate N dynamics demonstrated the need for determination of digestate N release pattern and rate (i.e., potentially mineralizable N parameters) for more efficient management of this product in cropping systems (Thomas et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic digestion of agricultural residues may be considered ecologically sound (Insam et al 2015), but the variation in digestate N concentrations and decomposition of digestate's organic N leads to uncertainties in recommendation rates for agricultural use. Previous studies on digestate N dynamics demonstrated the need for determination of digestate N release pattern and rate (i.e., potentially mineralizable N parameters) for more efficient management of this product in cropping systems (Thomas et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the results, after drying the fermentation residue is suitable for use as nutrient replenishment, and without loss of yield to replace fertilizers and liquid cow manure. Thomas et al (2017) investigated not only organic fertilizer, matured fermentation liquid, and solid separated matter, but also supplemented this with the already pelletized fermentation residue, during which the effects of the individual fertilizer pulp on autumn barley were measured for four years. On the basis of their results, during the fermentation and processing, the material undergoes substantial internal changes in content until it becomes pellet.…”
Section: Ingredients and Fertilization Effects Of Separated Biodieselmentioning
confidence: 99%
“…Nitrogen absorption was the lowest in the case of pellets, at only 2%, while it was highest in the matured fermentation liquid, at 41%. In addition, it was argued that pellet from fermented sludge could be an effective, but slow-release nutrient source, while also providing carbon replenishment [56].…”
Section: Ingredients and Fertilization Effects Of Separated Biodieselmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of digestate and the fertilising effect is assumed to be approximately the same as for manure [44,45]. It was also assumed that there is no need to invest in new spreading equipment.…”
Section: Calculation Of Economic Profitmentioning
confidence: 99%